2015
DOI: 10.1021/acs.iecr.5b02020
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in CO2 Adsorption on Hydrotalcite-based Material by Novel Carbon Support Combined with K2CO3 Impregnation

Abstract: In recent years, a great deal of interest has been shown for high-temperature adsorption of CO 2 on hydrotalcitelike compounds (HTlcs). Numerous efforts have been undertaken to enhance the CO 2 capture property of HTlcs, including alkali-metal impregnation, use of support materials, and modification of chemical composition. The present work demonstrates the applicability of coal-derived graphitic material (CGM) as an effective support for neat as well as K 2 CO 3 -promoted Mg−Al HTlc, enhancing the CO 2 adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Since the main active component of the layered double hydroxide (LDH)-based CO 2 adsorbent is also MgO [49][50][51][52] , much work has also been performed on the modification of MgO-based mixed oxides adsorbents derived from LDHs with molten salts, as listed in http://engine.scichina.com/doi/10.1016/j.jechem.2017.06.005 [53][54][55][56][57][58] . In 2013, Li et al .…”
Section: Molten Salts-modified Mgo-based Mixed Oxides Adsorbentsmentioning
confidence: 99%
“…Since the main active component of the layered double hydroxide (LDH)-based CO 2 adsorbent is also MgO [49][50][51][52] , much work has also been performed on the modification of MgO-based mixed oxides adsorbents derived from LDHs with molten salts, as listed in http://engine.scichina.com/doi/10.1016/j.jechem.2017.06.005 [53][54][55][56][57][58] . In 2013, Li et al .…”
Section: Molten Salts-modified Mgo-based Mixed Oxides Adsorbentsmentioning
confidence: 99%
“…(Espinal and Morreale, 2012). The adsorption of CO2 on solid materials works through weak physisorption or chemisorption interaction and is mostly employed in cyclic, multi-module processes of adsorption and desorption in which desorption is induced by pressure or temperature swing (Choi et al, 2009) Activated carbons, alkaline earth metal-oxides, hydrotalcites, (Bhatta et al, 2015) supported amines, (Shakerian et al, 2015;Yu et al, 2012) zeolites, (Krishna and van Baten, 2010). Covalent Organic Frameworks (COFs) (Diaz and Corma, 2016;Olajire, 2017) as well as MOFs (Zhou et al 2012;Sabouni et al, 2014;Verdegaal et al, 2016) are all examples of this class of adsorbents (Li et al, 2017;Sumida et al, 2012) Activated carbons have been reported to have a CO2 uptake of 4 mmol/g and a selectivity of CO2/N2 near 10 at room temperature and 1 bar (Berlier and Frère, 1996).…”
Section: Scheme 4: Base Catalysed Hydration Of Co2 To Bicarbonatementioning
confidence: 99%
“…Adsorption capacity of LDH could be enhanced by composite with porous supporting materials such as zeolites, activated carbon and Mesoporous silica. Bhatta et al [31] reported that in order to improve the adsorption capacity of LDH and keep the best reaction temperature, they found a kind of coal based porous carbon material, which was an economical natural source of carbon. Pramod et al [32] synthesized LDH-SBA-15 composite materials, which were mesoporous, versatile, eco-friendly and repeatable CO 2 capture materials.…”
Section: Advances In Engineering Research Volume 129mentioning
confidence: 99%